Effects of Malfunctions in Supply Chain Management on Company Revenues - Çiçek, Hasan (International Journal of Supply Chain Management, 2020)
This paper presents issues related to the effects of malfunctions in supply chain management on company revenues and profits. Case problems are presented that show the remarkable effects of supply chain management on company operations. The necessary steps that should be followed to improve company operations through appropriate supply chain management are also presented.Â